Characterization of Woody and Shrubby Vegetation in Synanthropic Forests Using Three-Dimensional Laser Scanning Technology - Alla Philippova; Natalia Stroiteleva; Dmitry Gura (Forest Science and Technology)
This study encompasses an analysis of the floristic composition of synanthropic vegetation within the forest zone of the Krasnodar Krai, exemplified by the Krasnyi Les, from 2010 to 2023. Synanthropic species, those that thrive in human-modified environments, were the primary focus of this study. Monitoring was conducted across five sites with varying ecotopic conditions, employing three-dimensional laser scanning to analyze vegetation structure. The research findings identified 54 species of woody and shrubby plants belonging to 37 genera and 22 families. The 3D laser scanning method significantly enhances the accuracy and detail of vegetation analysis compared to traditional methods, contributing to the identification of 4.2% additional taxa, primarily from the Rosaceae and Polygonaceae families. This approach enables a more precise assessment of vegetation spatial structure, including point cloud density and tree canopy height, thereby providing a more comprehensive and objective representation of the floristic composition. Furthermore, the application of laser scanning substantially improves monitoring efficiency and facilitates the analysis of vegetation in complex ecotopes with a high degree of accuracy. These findings can inform the development of conservation and forest resource management programs, as well as practical recommendations for biodiversity preservation in synanthropic forests of the Krasnodar Krai and analogous forests elsewhere in the world in terms of species composition.